Two- to five-year follow-up of 78 patients after treatment with the Flow Redirection Endoluminal Device - Lücking, Hannes; Dörfler, Arnd; Gölitz, Philipp; Engelhorn, Tobias; Lang, Stefan; Hölter, Philip (Interventional Neuroradiology, 2019)
Background and purpose Flow-diverter stents are well-established for the treatment of cerebral aneurysms. Flow Redirection Endoluminal Device differs from other flow-diverter stents by its dual-layer design and has proved equality to other devices in numerous short-term surveys. However, follow-up data covering substantially more than one year are still limited for this device. We present our long-term experience with Flow Redirection Endoluminal Device.
CRIS-Team WoS Importer:2019-10-22